A Perspective-Changing Teaching Experience in Araimiri - Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study underscores the remarkable human capacity for resilience and determination when confronted with challenging life situations. Specifically, this research delves into a teacher's interactions with a group of high school students who, due to their unique circumstances, embarked on a transformative journey, overcoming obstacles in the realm of education. The research focused on a private school in Araimiri in the Gulf Province of Papua New Guinea. Employing a qualitative methodology, the study specifically adopts an autoethnographic approach. This autoethnography unfolds against the backdrop of a unique and immersive experience, exposing the researcher to the intricate social dynamics, behaviors, and practices of a group of students. Through keen observations, profound conversations, shared experiences, and the examination of artifacts, the study offers an in-depth and distinctive perspective on the educational landscape during the specified period. The study sought to determine the circumstances that made the experiences of students and teachers significant, to identify key elements of the initial education-related situations of students, to determine the initiatives made to help students improve academically, and to reveal significant findings that manifested through the analyses of the experience. These are the conclusions of the study. First, teachers’ awareness of students' struggles and unique conditions helps them strengthen their teaching approaches. Second, students’ commitment to their lead role in the education process is imperative. Third, teachers’ depth in the understanding of topics and their commitment to teaching help in the ability to simplify complex concepts. Fourth, students’ prerequisite capabilities when introducing new lessons reinforce learning. Fifth, the implemented curriculum should match with relevant assessments that are often provided by the government or industry. These conclusions imply that educational processes are multifaceted and interconnected with components that have to be harmonized to ensure effectiveness.